Seismic behavior of the shallow clayey basins subjected to obliquely incident wave - Khanbabazadeh, Hadi; Iyisan, Recep; Ozaslan, Bilal (Techno-Press, 2022)
Under the effects of the near-field earthquakes, the incident angle of the incoming wave could be different. In this study, the influences of some parameters such as incident angle, basin edge, peak ground acceleration level of the bedrock motion as well as different clay types with different consistency on the amplification behavior of the shallow basins are investigated. To attain this goal, the numerical analyses of the basins filled with three different clay types are performed using a fully nonlinear method. The two dimensional models of the basins are subjected to a set of strong ground motions with different peak ground acceleration levels and three different incident angles of 30., 45. and 90. with respect to the horizontal axes. The results show the dominant effect of the obliquely subjected waves at most cases. The higher effect of the 45. incident angle on the basin response was concluded. In the other part of this study, the spectral amplification curves of the surface points were compared. It was seen that the maximum spectral amplification of different surface points occurs at different periods. Also, it is affected by the increase in the peak acceleration level of the incoming motions.
Keywords: basin edge effect; dynamic behavior; incident angle; numerical modeling; site effects